Chronic Use of Opioids for Nonmalignant pain: A Prospective Study - Perry N Fuchs; Ann Gamsa (Pain Research and Management)
OBJECTIVE: To assess the effects of long term opioid therapy on pain, mood, and social and leisure activities in patients with chronic nonmalignant pain.